Plasmas : the first state of matter - Krishan, V. (Vinod) (Cambridge : Cambridge University Press, 2013)
Most astronomers believe that the universe began about 15 billion years ago when an explosion led to its expansion and cooling. The present state of the universe compels us to believe that the universe was extremely hot and dense in its infancy. In the beginning there was intense radiation. The photons produced equal amounts of matter and antimatter and a plasma soup of particles and antiparticles was present. Plasma is the first state of matter from which all the other states originated. This book discusses the diversity of cosmic and terrestrial plasmas found in the early universe, galactic and intergalactic media, stellar atmospheres, interstellar spaces, the solar system and the Earth's ionosphere, and their observability with the most recent telescopes such as the Chandra X-ray telescope and gamma ray telescopes. It deals with different ways of creating plasmas such as thermal, pressure and radiative ionization for laboratory and cosmic plasmas.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Plasma (Ionized gases)